2022
DOI: 10.21608/ejchem.2022.159976.6894
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and Antibacterial Properties of synthesis Silver Nanoparticles with Nigella arvensis Aqueous Extract

Abstract: As a result of the emergence of new virus strains and the synthetics, virus infections pose significant global health challenges, so the need for new therapeutic drugs rises as new vi and bacterial infectious diseases emerge. This study aimed to synth extract and investigate their possible antiviral and antibacterial properties. X microscopy, and UV-Visible spectroscopy were used to validate the synthesis of Ag-NPs production through the shift from yellow color to dark brown color. TEM examination of Ag nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Nevertheless, only a small number of them have been used for therapeutic against viruses. A logical hypothesis would be to begin researching the properties and advantages of GB extract and Ag NPs as an antiviral versus the MERS-CoV and HCoV-229E based on our prior work on the conjugation of GB extract as a natural product and Ag NPs as an environmental nanoparticle synthesis [ 12 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, only a small number of them have been used for therapeutic against viruses. A logical hypothesis would be to begin researching the properties and advantages of GB extract and Ag NPs as an antiviral versus the MERS-CoV and HCoV-229E based on our prior work on the conjugation of GB extract as a natural product and Ag NPs as an environmental nanoparticle synthesis [ 12 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the transitional elements, silver nanoparticles (Ag NPs) are a novel nanometal particle form widely incorporated in biological, therapeutic, and engineering disciplines [ 10 ]. In particular, synthetic biologically active Ag NPs have demonstrated substantial therapeutic aptitudes, including broad-spectrum antimicrobial, anticancer, anti-inflammatory, antioxidative, and antidiabetic action [ 11 , 12 ]. A modern review of the synthesis of Ag NPs and their uses in antimicrobial textile fabrics, food packaging films, and wound dressings is provided by Chengzhu L. et al The antibacterial activity and cytotoxic effect in mammalian cells are given special consideration [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Te Ag ions could be reduced by the action of favonoids, alkaloids, and polyphenols in the N. sativa seed extract [66]. [ [69][70][71][72]. Tis analysis revealed that nanoparticles are orthorhombic crystals.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that argan oil has antibacterial activity against methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa . Moreover, the studies indicated that treatment with argan oil alone did not yield any or had very low antibacterial activity against methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa , respectively ( Naher et al, 2014 ; Elnosary et al, 2022 ). A study by Stojkovic et al (2013 ) found that the naturally occurring compounds, caffeic acid, p-coumaric acid, and rutin, present in argan oil could inhibit Staphylococcus aureus growth.…”
Section: Discussionmentioning
confidence: 99%